Manager migration, learning‐by‐hiring, and cultural distance in international soccer. (12th August 2019) - Peeters, Thomas L. P. R.; Mills, Brian M.; Pennings, Enrico; Sung, Hojun
Abstract: Research Summary : We investigate the international transfer of managerial know‐how by analyzing manager migration patterns in the setting of international soccer. We characterize a country's managerial know‐how by estimating a stochastic frontier model, which relates the country's soccer performance to socioeconomic and climatic conditions. We find evidence of learning‐by‐hiring in that hiring a migrant manager hailing from a high know‐how country is beneficial to the destination country's performance. Larger cultural distance between the migrant manager and destination country reduces the effectiveness of learning‐by‐hiring, but this effect is moderated by the migrant manager's prior international experience. The transfer of managerial know‐how contributes to the overall convergence of low‐performing versus high‐performing soccer countries. Managerial Summary : In this study, we ask whether firms in developing countries, which often suffer from having low‐quality management practices, can improve their performance by hiring managers from developed countries, who may implement better management practices. We investigate this in the context of national soccer team competition, because this allows us to track the performance of migrant managers very precisely over time. We find that hiring a migrant manager from a developed soccer country improves the performance of the developing host country. This performance improvement is smaller when the migrant's country of origin is culturally very different from the host, but migrant managers with extensive international experience are able to overcome this negative effect of cultural distance.